Biodegradation of p‐cresol and sulfide removal by a marine‐denitrifying consortium. (24th November 2014) - Meza‐Escalante, Edna R.; Alvarez, Luis H.; Serrano, Denisse; Mendoza, Erika; Bonola, Ramsés
Abstract The simultaneous removal of sulfide and p‐cresol was carried out by using a marine‐denitrifying consortium collected in the coastal zone of Sonora, Mexico. Different experimental conditions were used to evaluate the capacity of the consortium to simultaneously eliminate nitrate, sulfide, and p‐cresol. For instance, the first set of assays was conducted at different sulfide concentrations (20, 50, and 100 mg S2− L−1), with a fixed concentration of p‐cresol (45 mg C L−1). The second set of assays was developed at different concentrations of p‐cresol (45, 75, and 100 mg C L−1), in the presence of 20 mg S2− L−1. In all cases, the concentration of nitrate was stoichiometrically added for the complete oxidization of the substrates. The results showed removal efficiencies up to 92% for p‐cresol and nitrate at 20 and 50 mg S2− L−1; whereas at 100 mg S2− L−1 removal efficiencies were 77% and 59% for p‐cresol and nitrate, respectively. On the other hand, sulfide (20 mg L−1) was completely removed under different concentrations of p‐cresol tested, with a partial accumulation of nitrite according to the increment of p‐cresol concentration. The results obtained indicate that the marine consortium was able to simultaneously remove the pollutants studied.